Kenneth Bancroft Clark papers - Clark, Kenneth Bancroft, 1914-2005.; City University of New York. City College. Social Dynamics Research Institute; Clark, Phipps, Clark, and Harris; Kenneth B. Clark and Associates; Metropolitan Applied Research Center; Universal Negro Improvement Association
Correspondence, memoranda, minutes, speeches, writings, reports, transcripts of interviews and testimony, subject files, project files, academic files, administrative files, financial records, family papers, secondary background material, printed matter, photographs and other papers relating chiefly to Clark's career as a psychologist and professor at the City College, City University of New York, and his contributions to the African American civil rights movement and equal educational opportunities. Subjects include the psychological effects of racial discrimination and segregation; school integration; Brown v. Board of Education of Topeka; riots in Harlem, New York, N.Y.; the integration of public schools in Little Rock, Ark.; public school systems of New York, N.Y., and Washington, D.C.; the work of psychologist Otto Klineberg; the American Psychological Association; New York State Urban Development Corporation; and the Board of Regents, University of the State of New York.
Also includes records of the Social Dynamics Research Institute, City College, City University of New York; of the consulting firm Clark, Phipps, Clark, and Harris, and of its successor, Kenneth B. Clark and Associates; of the Central Division, Brooklyn , N.Y., of Marcus Garvey's Universal Negro Improvement Association; and of the Metropolitan Applied Research Center (MARC), a group Clark organized in New York, N.Y., to advocate for the urban poor and disadvantaged. The MARC records include files pertaining to the Hastie Group (also known as the Haverford Group), an assembly of black educators and professionals discussing black separatism.
Clark's work with his wife, child psychologist Mamie Phipps Clark, with whom he founded the Northside Center for Child Development, New York, N.Y., is also documented. Other affiliations represented include Harlem Youth Opportunities Unlimited (HARYOU), Intergroup Committee on New York's Public Schools, Mid-Century White House Conference on Children and Youth, National Association for the Advancement of Colored People, National Child Labor Committee, National Scholarship Service and Fund for Negro Students, and Society for the Psychological Study of Social Issues.
Correspondents include Gordon W. Allport, Robert L. Carter, Hubert T. Delany, Thurgood Marshall, Alfred Lee McClung, Daniel P. Moynihan, Gardner Murphy, A. Philip Randolph, Louis L. Redding, and Elizabeth Waring.
In part, microfilm of selected addresses, reports, and other material of originals in the collection and in private hands
Library of Congress Geography and Map Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Psychologist, author, and educator.
Collection material in English.
Keywords: Allport, Gordon W. -- 1897-1967 -- Correspondence; Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc; Carter, Robert L., -- 1917-2012 -- Correspondence; Clark, Mamie Phipps; Delany, Hubert T. -- Correspondence; Garvey, Marcus, -- 1887-1940.; Klineberg, Otto, -- 1899-1992.; Marshall, Thurgood, -- 1908-1993 -- Correspondence; McClung, Alfred Lee -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Murphy, Gardner, -- 1895-1979 -- Correspondence; Randolph, A. Philip -- 1889-1979 -- Correspondence; Redding, Louis L. -- Correspondence; Waring, Elizabeth -- Correspondence; Clark family; Topeka (Kan.). -- Board of Education -- Trials, litigation, etc; American Psychological Association; City University of New York. -- City College -- Faculty; HARYOU (Organization); Hastie Group; Haverford Group; Intergroup Committee on New York's Public Schools; National Association for the Advancement of Colored People; National Child Labor Committee (U.S.); National Scholarship Service and Fund for Negro Students; New York State Urban Development Corporation; Northside Center for Child Development; Society for the Psychological Study of Social Issues; University of the State of New York. -- Board of Regents; African Americans -- Civil rights; African Americans -- Education; African Americans -- Scholarships, fellowships, etc; African Americans -- Societies, etc; Black nationalism -- United States; Child development; Child labor; Children with social disabilities; Civil rights -- United States; Discrimination in education; Education; Poor -- New York (State) -- New York; Psychology -- Research; Psychology -- Societies, etc; Public schools -- New York (State); Public schools -- New York (State) -- New York; Public schools -- Washington (D.C.); Race discrimination -- Psychological aspects; Riots -- New York (State) -- New York; School integration; School integration -- Arkansas -- Little Rock; Segregation -- Psychological effects; Youth with social disabilities; Harlem (New York, N.Y.) -- Social conditions; Authors; Educators; Psychologists